Dodging the potholes: the spatio-distribution and socio-economic impacts of potholes in the residential areas of Gweru, Zimbabwe - Mutekwa, Timothy; Matsa, Mark; Kanyathi, Kudzanai (David Publishing, 2014)
Since the year 2000, the city of Gweru has had an unprecedented proliferation of unattended potholes on most of its roads. These potholes have caused discomfort to the motoring public, caused death to others and damaged vehicles. This paper presents the results o f a study that sought to establish the spatial distribution of potholes and determine their socio-economic impacts in Gweru’s residential areas. Pothole location and dimensions were measured in the field whilst interviews and questionnaires were administered to vehicle owners, motor mechanic experts, drivers and the travelling public to determine their socio-economic and mechanical impacts. Stratified, convenience and purposive sampling methods were used in the selection of study streets and respondents to questionnaires and interviews. Results revealed that potholes are more concentrated in high density residential areas compared to low density areas. This is primarily due to the substandard construction of roads done in high density residential areas. Other causes of pothole formation identified during this study are poor drainage on the roads, rainfall impact, advanced age of roads, poor or lack of maintenance, type and volume of traffic as well as the effect of tree-root prying on paved surfaces. It is recommended that Gweru City Council enters into partnerships in road construction. The city should also establish fundraising projects to augment its budget. This would help ease problems of service delivery including road maintenance. Signposts can be erected to warn drivers about these hazards in the most affected streets and suburbs. It is also important that council set aside a toll-free telephone line link with road users so that areas where new potholes have been detected are quickly reported and attended to. This will not only save lives but also reduce road maintenance costs and vehicle damage.